Research on occupational health and safety management in the context of big data - Qianrui Hwang; Min Yao; Min Yao; Shugang Li; Fang Wang; Zheng Li; Tongshuang Liu (Frontiers Media S.A., 2024)
At present, with the rapid development of China's economy and industrial transformation, the situation of China's occupational health and safety is grim, and at this stage, there are still problems such as unsound laws and regulations and standard system, weak awareness of the primary responsibility of the enterprise, weak supervisory, technical capacity, and backward application of information technology. Based on the current situation of occupational health and safety management at home and abroad and relevant theories, this study adopts the method of systematic review and takes the evaluation of China's occupational health and safety management system as the theme and conducts a valuable exploration of the evaluation research of China's occupational health and safety management system, analyzes the current situation of occupational health and safety from the aspects of prevention and control of occupational diseases, prevention and control of safety accidents, and monitoring of the psychology of insecurity, and researches the two aspects of governmental regulation and social responsibility It analyzes the current situation of occupational health and safety from the aspects of prevention and control of occupational diseases, prevention and control of safety accidents and monitoring of unsafe psychology, and studies the current situation of post-performance evaluation of the development of OHS management system from the aspects of government supervision and social responsibility, aiming at providing countermeasure suggestions for the sustainable development of OHS management system in China. The research indicates that in the context of the new economic normal, effectively safeguarding workers' occupational health rights and interests, promoting sustainable and robust economic and social development, as well as enhancing the sustainability of China's occupational health and safety management system have emerged as challenging yet pivotal areas for comprehensive exploration.